2016
DOI: 10.18632/oncotarget.11325
|View full text |Cite
|
Sign up to set email alerts
|

Targeting a novel cancer-driving protein (LAPTM4B-35) by a small molecule (ETS) to inhibit cancer growth and metastasis

Abstract: Our previous studies demonstrated that LAPTM4B-35 is overexpressed in a variety of solid cancers including hepatocellular carcinoma (HCC), and is an independent factor for prognosis. LAPTM4B-35 overexpression causes carcinogenesis and enhances cancer growth, metastasis and multidrug resistance, and thus may be a candidate for therapeutic targeting. The present study shows ethylglyoxal bisthiosemicarbazon (ETS) has effective anticancer activity through LAPTM4B-35 targeting. Bel-7402 and HepG2 cell lines from hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A number of studies have shown that the proliferation of cells overexpressing LAPTM4B is closely correlated with tumor progression and metastasis [ 20 , 21 ]. In our study, increased LAPTM4B expression was strongly associated with prognosis-related features, including tumor size, TNM stage and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the proliferation of cells overexpressing LAPTM4B is closely correlated with tumor progression and metastasis [ 20 , 21 ]. In our study, increased LAPTM4B expression was strongly associated with prognosis-related features, including tumor size, TNM stage and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Akt and mTOR overexpression improved the protective effects after cerebral ischemia-reperfusion injury in MCAO rats, suggesting that the activation of the PI3K/Akt/mTOR signaling pathway provides significant neuroprotective effects against cerebral ischemia-reperfusion injury. P-Akt and p-mTOR ( Li et al, 2016 ; Yang et al, 2017 ; Park et al, 2019 ; Sun et al, 2020 ) are commonly recognized as markers for activation of the PI3K/Akt/mTOR pathway. In the present study, the levels of p-AKT and p-mTOR were significantly decreased following I/R injury and were activated by TFCJ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…LAPTM4B was also associated with tumor proliferation, angiogenesis, and poor prognosis in patients with glioblastoma, which could be used as a potential novel prognostic marker of glioblastoma to improve its treatment ( 35 ). Ethylglyoxal bisthiosemicarbazon, a specific inhibitor of LAPTM4B, was found to have effective antitumor activity in HCC ( 36 ).…”
Section: Discussionmentioning
confidence: 99%